Identification and functional characterization of EseH, a new effector of the type III secretion system of Edwardsiella piscicida. (26th July 2016) - Hou, Mingyu; Chen, Ran; Yang, Dahai; Núñez, Gabriel; Wang, Zhuang; Wang, Qiyao; Zhang, Yuanxing; Liu, Qin
Summary: Edwardsiella piscicida, a bacterial pathogen in fish and humans, expresses a type III secretion system (T3SS) that is critical for pathogen virulence and disease development. However, little is known about the associated effectors and their functional importance. In this study, we identified the ETAE_1757 encoded protein, termed here E. piscicida secretion effector H (EseH) as a novel T3SS effector. We found that upon infection with E. piscicida, EseH is translocated into nucleus of host cells which required the T3SS. Homology modelling analysis suggests that EseH is an enzyme that belongs to the family of phosphothreothine lyases. Consistently, EseH inhibited phosphorylation of ERK1/2, p38α and JNK MAPK pathways in host cells, but had no effect on the NF‐kB pathway. Furthermore, mutation of the critical amino acid residues predicted to confer phosphothreonine lyase activity abolished the ability of EseH to inhibit phosphorylation of ERK1/2, p38α and JNK MAPK pathways in host cells. In addition, we found an increase in transcript levels of TNF‐α, IL‐12, IL‐10 and IFN‐γ in zebrafish infected with the eseH mutant when compared with the wild type bacterium. Importantly, the virulence of E. piscicida deficient in EseH was highly attenuated in the zebrafish infection model which correlated with decreased loads of the mutant bacterium in both liver and kidney. Complementation of the E. piscicida mutant strain with EseH restored virulence in zebrafish. These results identified EseH as a critical T3SS effector that contributes to virulence by targeting MAPK signalling during E. piscicida infection.